Evaluating the emission benefits of shared autonomous electric vehicle fleets: A case study in California. (1st October 2022) - Li, Yanning; Li, Xinwei; Jenn, Alan
Highlights: We evaluate the emissions from SAEVs with a grid operation model. SAEV charging demand is simulated using real-world data from TNCs. In the Californian grid, SAEVs are more than 5 times less CO2 intensive than ICVs. Emission benefits of SAEVs increase with the expansion of renewable generation. Synergizing SAEV charging with grid operation yields substantial emission benefits. Abstract: The transportation sector is a major source of greenhouse gas (GHG) emissions. Shared autonomous electric vehicles (SAEVs) have the potential to mitigate emissions, but the effect can be highly dependent on the growth and operation of the SAEV fleet as well as its interaction with the evolving power system. In this study, we simulate travel and charging behaviors of SAEVs based on empirical data of ride-hail service operations, and integrate SAEV charging with the Grid Optimized Operation Dispatch (GOOD) model, taking into account the expansion of renewable generation and charger capacity over time. Emissions from SAEVs are compared across different market adoption levels, occupancy rates, and charging strategies. We find that under the Californian power grid, SAEVs are generally more than 5 times less carbon intensive than modern day ICVs on a per mile basis. The extent of aligning charging schedule with renewable generation is an essential determinant of the economic and emission impact from an SAEV fleet. At higher levels of renewable penetration, synergizing SAEV charging with grid operation can be the most impactful means to reduce emissions from an SAEV fleet, generating up to 95% less emissions than other charging strategies. We also examine the introduction of a carbon tax and find that it can further amplify the advantage of smart charging by approximately 1.5 times in the cost-effectiveness of emission mitigation.